Identification of Follower Status Based on Male Proximity Score in Crested Macaque - Andre Pasetha; Lisa Michelle Danish; Dyah Perwitasari-Farajallah; Muhammad Agil; Antje Engelhardt (Bogor Agricultural University, Indonesia, 2020)
Crested macaque live in multimale-multifemale social groups where temporary association (consortship) typically occurs. Current theory and these limited qualitative observations suggest the hypothesis that behavior functions as a means for males to gain access to fertile females. The aim of this study was to investigate follower status based on quantitative method. Males were classified as either “consort males,” “followers,” and “non-followers” based on proximity maintanance every 15 minute uses scan sampling. Tactics used by followers were classified into 1) individual challenge, 2) coalitionary challenge, 3) abandoned takeover, and 4) opportunistic takeover. The proportion of successful takeovers by followers was calculated by dividing the number of takeovers by followers by the total number of observed takeovers. The proportion of followers is higher than average on D-5 and earlier, D-4, and D-3. Only two of the four consort takeover tactics were used by followers. For abandoned which made up 40% and for individual tactic was made up to 11.5% of consort takeovers tactic used. This study contribute to our understanding of alternative mating strategy in primate and provide the first quantitative data demonstrating that following is an alternative mating strategy in crested macaque (Macaca nigra).